KESERUPAAN HIDUP ORANG SUNDA DALAM KOMIK ADEN ENDUL - Kasmana, Kankan (Universitas Komputer Indonesia, 2020)
Aden Endul a comic strip that was present in West Java Indonesia starting in 1986. With comedy genre, comic raised the theme about Sundanese people (a tribe who inhabit West Java) daily life. This article discusses the comic Aden Endul, as the literary image, seeks to find aspects of Sundanese culture in narration and visual, through structural analysis. The result of the research revealed that comics represent Sundanese culture aspect in the form of Sundanese language usage which shows the teachings of silih asah, silih asih and silih asuh, religious aspect; the syncretism of Sundanese and Islamic teachings, the view of the life of traditional society whose close to nature. The organization of comic composition along with its elements shows the comic artist's knowledge as a Sundanese, possessing an aspect of visuality that presents life experiences and comic life. The humor is intented as an autocritical for the comic artist and also readers.